Study of the influence of alkalized cocoa powder on the structural and mechanical properties of instant mousses - Rubanka, Kateryna; Gorodyska, Olena (My University, 2020)
Робота присвячена дослідженню впливу алкалізованого какао-порошку на процес приготування мусів. Проведена порівняльна оцінка впливу різних видів какао-порошків на піноутворюючу здатність мусів, їх мікроструктуру, структурно- механічні показники та органолептичні властивості. Встановлено оптимальне дозування алкалізованого какао-порошку до рецептури мусів швидкого приготування.

The work is devoted to the study of the influence of alkalized cocoa powder on the process of making mousses. A comparative assessment of the influence of various types of cocoa powders on the foaming ability of mousses, their microstructure, structural and mechanical characteristics and organoleptic properties was carried out. The optimal dosage of alkalized cocoa powder in the recipe for instant mousses has been established.
Keywords: кафедра технології консервування; какао-порошок; мус; структурно-механічні властивості; піноутворююча здатність; cocoa powder; instant mousse; foaming ability